Five million years in the darkness: A new troglomorphic species of Cryptops Leach, 1814 (Chilopoda, Scolopendromorpha) from Movile Cave, Romania - Vahtera V; Stoev P; Akkari N (Pensoft Publishers, 2022)
A new species of Cryptops Leach, 1814, C. speleorex sp. nov., is described from Movile Cave, Dobrogea, Romania. The cave is remarkable for its unique ecosystem entirely dependent on methane- and sulfur-oxidising bacteria. Until now, the cave was thought to be inhabited by the epigean species C. anomalans, which is widespread in Europe. Despite its resemblance to C. anomalans, the new species is well-defined morphologically and molecularly based on two mitochondrial (cytochrome c oxidase subunit I COI and 16S rDNA) and one nuclear (28S rDNA) markers. Cryptops speleorex sp. nov. shows a number of troglomorphic traits such as a generally large body and elongated appendages and spiracles, higher number of coxal pores and saw teeth on the tibia of the ultimate leg. With this record, the number of endemic species known from the Movile Cave reaches 35, which ranks it as one of the most species-rich caves in the world.